Model Tracking Pembicara Dalam Perekaman Video Otomatis Pada Kelas Cendekia - Elga Ridlo Sinatriya; Muhammad Idham Ananta Timur; Ika Candradewi (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2019)
The requisite of intelligent classroom’s saving the information from speakers inside the class using ubiquitous computing concept. It said the most profound technologies are those that disappear, and they weave themselves into fabric of everday life until they are indistinguishable from it. It requires a few capability such as tracking the speaker and record it. Therefore it will be require the system that can tracking the speaker in real time, ignore the other speaker, and recording speaker’s activity. The system consumes 168.02 ms in one move, like detection using statis camera, send the centroid to microcontroller, second detection using dinamis camera, and record it. The system had an accuracy of 93.37 % to fits the speaker at the middle of frame record. The system is also had an accuracy of 98%  to detecting the correct speaker.